KEPEMIMPINAN KEPALA MADRASAH DALAM UPAYA MENINGKATKAN MUTU PENDIDIKAN DI MAN 2 BATUSANGKAR KABUPATEN TANAH DATAR - Nurlela Nurlela; Marhen Marhen (IAIN Batusangkar, 2019)
This research is motivated because MAN 2 Batusanggkar already brought positive changes to the collar in the quality of schooling. This is evidenced by the many religious programs, science, scouts, sport and art that have been realized. The program that has been realized is a scout camp between schools of West Sumatra, calligraphy training, development of new classes, building and other art. As for the purpose of this research is because they want to understand the phenomenon of the leadership of Principal in an effort to improve the quality of education in MAN 2 Batusanggkar Tanah Datar Distric and to look for the meaning behind the facts about the leadership of Principal in an effort to improve the quality of education in MAN 2 Batusanggkar Tanah Datar Distric. Research method in this research is a qualitative. The qualitative research is a research procedure with the results of descriptive data. In collecting the data, researchers conducted observation, direct interviews and documentation study. Observation, direct interviews and documentation study that examined do is about the leadership implementation of head master to improve quality of education in MAN 2 Batusanggkar Tanah Datar District. The results of this research showed (1). MAN 2 Batusanggkar school principals have the multi-style leadership, in carrying out their duties this kind of leader would welcome suggestions from subordinates and even critics ask of them for the successful joint work. (2). The strategy used in general is a bridge between the hearts of human resources, the division of tasks in accordance with the competency of teachers, there is a clear timetable, the evaluation of direct and indirect evaluation, and each teacher mengahargai each other and help each other. (3). Internal constraints are still many areas of learning of human resources, has not yet formed groups by subject, lack of funding and very limited assistance, institutionally, MAN 2 Batusanggkar in designing the budget does not have the autonomy and the large amount of human resources and input in MAN 2 Batusanggkar. External obstacle is cooperation with the local government in the context of religious education is still limited and the quality improvement program that institution under the name of Madrasah in the field of religion is often powerless against the current globalization. Thus, the principal's leadership in improving the quality of education is done by applying multi-style leadership and multi-strategy. Although there are some constraints, but the constraints can be resolved properly.